The social setting of Jesus and the gospels - Stegemann, Wolfgang; Malina, Bruce J.; Theißen, Gerd (Fortress Press, 2002)
Social-scientific methods in historical Jesus research / Bruce J. Malina -- Ethnocentrism and historical questions about Jesus / Richard L. Rohrbaugh -- The contextual ethics of Jesus / Wolfgang Stegemann -- Jesus as fatherless child / Andries van Aarde -- Jesus heals the hemorrhaging woman / Stuart L. Love -- Altered states of consciousness in the synoptics / John J. Pilch -- Jesus and the demoniacs / Christian Strecker -- The baptism of Jesus : a ritual-critical approach / Richard E. DeMaris -- The politics of exoricsm / Santiago Guijarro -- The historical Jesus and honor reversal at the table / S. Scott Bartchy -- Jesus and the reduction of intergroup conflict / Philip F. Esler -- The plague of uncleanness? : The ancient illness construct "issue of blood" in Luke 8:43-48 / Annette Weissenrieder -- The political dimension of Jesus' activities / Gerd Theissen -- The political Jesus : discipleship and disengagement / T. Raymond Hobbs -- Jesus and the social bandits / K.C. Hanson -- The Jesus movement and network analysis / Dennis C. Duling -- Money in the moral universe of the New testament / Douglas E. Oakman -- Gifts, tributes, and offerings / Gary Stansell -- The Gospels in comparison with the Pauline letters : what we can learn from social-scientific models / Albert Verdoodt.
Includes bibliographical references and indexes
Keywords: Jesus Christ; Bible -- Gospels -- Social scientific criticism; Bible -- N.T -- Gospels -- Social scientific criticism; Palestine -- Social life and customs -- To 70 A.D; Bibel / Evangelien; Jesus Christus